Kepuasan Petani Terhadap Keberadaan Pupuk Bersubsidi di Kecamatan Siding Kabupaten Bengkayang - Kutriana, Kutriana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Subsidized fertilizer is a government assistance to help farmers obtain fertilizer at affordable prices and increase agricultural yields. The purpose of this study is to examine the level of farmer satisfaction with the existence of subsidized fertilizer in Siding District, Bengkayang Regency and to examine the attributes that influence farmer satisfaction with the existence of subsidized fertilizer in Siding District, Bengkayang Regency. This study was conducted in Siding District, Bengkayang Regency. Data collection methods were observation, interviews and documentation while data analysis methods used CSI analysis and IPA analysis with the help of excel and SPSS. The results of the CSI analysis study showed that the level of farmer satisfaction with the existence of subsidized fertilizer in Siding District, Bengkayang Regency was reviewed from five variables; quality: 88.74%, seller service: 89.53%, price: 88.01%, availability: 89.76% and information: 86.96%. Based on the CSI value, the five variables are included in the category of very satisfied with the existence of subsidized fertilizer in Siding District, Bengkayang Regency, while the results of the IPA analysis show that important attributes that need to be maintained in order to maintain farmer satisfaction with the existence of subsidized fertilizer in Siding District, Bengkayang Regency are the friendliness of subsidized fertilizer sellers in serving farmers, easy requirements for taking subsidized fertilizer, farmers' assessment of the price of subsidized fertilizer and information about subsidized fertilizer provided to farmers is adequate and meets farmers' needs.